2008
DOI: 10.1016/j.rapm.2007.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic Effect of Lidocaine Patch 5% in the Treatment of Acute Herpes Zoster: A Double-Blind and Vehicle-Controlled Study

Abstract: This study demonstrates that lidocaine patch 5%, applied twice a day, could serve as a well tolerated and effective modality to relieve moderate to severe pain associated with acute herpes zoster presumably through its pharmacological action and physical barrier effect on sensitized skin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 18 publications
1
24
0
Order By: Relevance
“…A randomized controlled trial has shown that the lidocaine patch can provide significant pain relief in acute HZ but care should to taken to ensure that it is applied only to the area of intact skin. 24, 55 Topical capsaicin is an effective backup alternative in the treatment of PHN. 31 Unfortunately, most patients find the burning sensation from capsaicin intolerable so it is not recommended for acute pain from HZ.…”
Section: Treatmentmentioning
confidence: 99%
“…A randomized controlled trial has shown that the lidocaine patch can provide significant pain relief in acute HZ but care should to taken to ensure that it is applied only to the area of intact skin. 24, 55 Topical capsaicin is an effective backup alternative in the treatment of PHN. 31 Unfortunately, most patients find the burning sensation from capsaicin intolerable so it is not recommended for acute pain from HZ.…”
Section: Treatmentmentioning
confidence: 99%
“…Data are limited on the effectiveness of ketamine and amitriptyline, 54-59 but the evidence for the effectiveness of lidocaine and capsaicin is stronger. 54,56-58 In a randomized trial of 35 patients with non–cancer-related postherpetic, postoperative, or diabetes-related neuropathic pain, pain intensity was reduced with topical lidocaine but not with topical amitriptyline when compared with placebo. 57 A larger trial with a similar population of 92 patients found no effect of topical amitriptyline, ketamine, or a combination of the two.…”
Section: Management Of Painmentioning
confidence: 99%
“…Lidocaine (LID), an amide derivative, is a safer anaesthetic agent that possesses a mild local analgesic effect (10). The efficacy of combinatorial FLB and LID therapy has already been established for the propofol injection induced pain (11).…”
mentioning
confidence: 99%